OPINIONS OF SCIENTIFIC AND TECHNOLOGY TEACHER CANDIDATES ABOUT CONTRIBUTORS TO SELF TEACHING METHODS IN PHYSICS TEACHING - Cihat DEMİR (International Journal of Eurasia Social Sciences, 2018)
Physics is a profound thought that requires more abstract thinking skills than other classes, and is bound up with philosophy, and whose borders are boundaries of the universe. For this reason, there is a perception that it is difficult for students to learn physics. In physics teaching, researchers have done a lot of work to help teachers and prospective teachers in teaching their subjects to better understand the physics. It is estimated that one of the best lessons to assist prospective teachers to facilitate physics teaching is a course of special teaching methods. The purpose of this study is to reveal the contribution of special teaching methods to physics teaching according to the science and technology teacher candidates. The study group consists of 40 students studying in science and technology department at Dicle University Ziya Gökalp Faculty of Education in 2016-2017 education year. Qualitative research traditions have been adhered to in the survey on the screening model. As a data gathering tool, a semi-structured interview form with 5 questions prepared by the researcher was used. In the analysis of the data, the answers given by the teacher candidates are divided into categories and the percentage and frequency values are given. According to the results of the study; science and technology teacher candidates consider that the special teaching methods course will make a positive contribution to them in physics teaching. According to the results of the study, necessary suggestions were made to physics education researchers and related institutions.